Editorial: Bioenergy and biorefinery – biological solution for sustainable development of human society. Issue 6 (5th June 2015) - Qu, Yinbo; Wu, Wen‐Teng
<x xml:space="preserve">Abstract</x> The world is facing more and more severe challenges in energy supply and environmental pollution since 21st century, especially in Asia, which threaten to the sustainable development of human society.